The Effect of COVID-19 on College Students’ Entrepreneurial Intentions - Sheng, Fan; Chen, Yangyang (Frontiers in Psychology, 2022)
The new coronary pneumonia epidemic has had a tremendous impact on the world economic situation, causing a large number of enterprises to suffer serious losses, but also bringing a large number of entrepreneurial opportunities. For college students, whether the opportunities brought by the epidemic can attract them to step into the entrepreneurial path becomes a question worthy of attention in the process of restoring economic vitality and guiding students' employment and entrepreneurship. In this paper, a mediation model was constructed and tested through 245 questionnaire data by combining event system theory, regulatory focus theory, and emotion cognitive evaluation theory. The results showed that defensive regulatory focus and fear of failure, facilitative regulatory focus and fear of failure were all able to continuously mediate the effect of event intensity of the new coronary pneumonia epidemic on the entrepreneurial intentions of college students.